Effects of adding EDTA and Fe2+ on the performance of reactor and microbial community structure in two simulated phases of anaerobic digestion. (March 2019) - Cai, Yafan; Hu, Kai; Zheng, Zehui; Zhang, Yue; Guo, Shiyu; Zhao, Xiaoling; Cui, Zongjun; Wang, Xiaofen
Graphical abstract: Highlights: Ethylenediaminetetraacetic acid (EDTA) accelerated digestion process in both phases. EDTA can regulate the Fe-fractions which were closely related to Fe-bioavailability. The microbial community structure changed following by the change of Fe-fractions. EDTA proved its potential application value as a ligand of Fe. Abstract: The uptake of trace elements can be impeded by precipitation in the presence of carbonates and sulfates. The objective of this study was to investigate whether ethylenediaminetetraacetic acid (EDTA) enhances the performance of anaerobic digestion by forming dissolved complexes with Fe 2+ . Batch experiments were performed in this study and acidogenic and methanogenic phases were artificially simulated. EDTA was added to both of phases to examine its effects on Fe bioavailability, metabolic parameters and microbial community structure. The results showed that EDTA significantly accelerated the digestion process in both phases because its addition changed the Fe sorption law and increased Fe-bioavailability. The microbial community structure changed following by the change of Fe-fractions which was determined by EDTA. This study demonstrated that EDTA as ligand could increase the Fe-bioavailability and then reduced or replaced the addition of Fe.